Every 3-connected claw-free b{i;7-i}-free graph is Hamiltonian - Saburov, Khikmat; Ganiev, Inomjon; Saburov, Mansoor (2012)
In this paper we will proof that every 3-connected K{1;3}B{2;5} (or K{1;3}B{3;4})-free graph is Hamiltonian